Changes in Federal Environmental Policy in the 1990s - Keough, Paul (Maine Policy Review, 1992)
Paul Keough has served as the Deputy Regional Administrator of the New England office of the U.S. Environmental Protection Agency (EPA) for nearly 10 years. Among the changes in EPA’s approach to regulation in recent years are more emphasis on pollution prevention and more willingness to develop and apply voluntary and market-based approaches to environmental protection. For future environmental initiatives, Keough foresees greater emphasis on risk-management and greater flexibility in state-federal relations.